The Influence of Gadget Use on Moral Development: A Systematic Literature Review - Beni Zakaria Fitriyanto; Ahmad Syaifullah; Alfi Noer Diana Hafidah; Yasril Gunawan; Benny Prasetiya (Education Reserach Center, 2026)
This study aims to identify, analyze, and synthesize empirical findings concerning the influence of gadget use on the moral development of children and adolescents, based on reputable Scopus-indexed studies published within the past decade. The method employed is a systematic literature review utilizing the PRISMA approach, encompassing the selection of relevant empirical studies quantitative, qualitative, and longitudinal that examine variables related to gadget use, psychological processes such as empathy, self-regulation, and moral disengagement, as well as prosocial and antisocial behaviors. The results of the synthesis indicate that the impact of gadget use is neither direct nor linear; rather, it is moderated by factors such as duration of use, type of content consumed, digital literacy, parenting style, and the broader social environment. Moderate use accompanied by dialogic parental mediation has the potential to strengthen digital ethical literacy and promote prosocial behavior. Conversely, excessive use without supervision and exposure to negative content are associated with decreased empathy, heightened moral disengagement, and a greater propensity toward antisocial behavior.